2021
DOI: 10.1007/s10940-021-09501-0
|View full text |Cite|
|
Sign up to set email alerts
|

Global Crime Patterns: An Analysis of Survey Data from 166 Countries Around the World, 2006–2019

Abstract: Objectives This article explores the merits of commercially-based survey data on crime through cross-validation with established crime metrics. Methods Using unpublished data from 166 countries covering the period between 2006 and 2019, the article describes the geographical distribution across global regions and trends over time of three types of common crime, homicide, and organised crime. The article then explores possible determinants of the geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…But by the mid-1990s, several countries started to observe a widespread drop in crime, most notably the United states where violent and property crime indexes fell by 34% and 29%, respectively (Ceccato 2015d;Levitt 2004). More recently, van Dijk et al (2021) found, for instance, that rates of common crime as well as homicide have continued to drop in the Global North, in particular from 2006 to 2019, while Africa, South Asia, and Central America experienced an increase. However, not all forms of crime followed this trend; for instance, an exception being organized crime and corruption which decreased in sub-Saharan Africa and increased in North and Latin America, Australia, and parts of Europe.…”
Section: Crime Trendsmentioning
confidence: 99%
“…But by the mid-1990s, several countries started to observe a widespread drop in crime, most notably the United states where violent and property crime indexes fell by 34% and 29%, respectively (Ceccato 2015d;Levitt 2004). More recently, van Dijk et al (2021) found, for instance, that rates of common crime as well as homicide have continued to drop in the Global North, in particular from 2006 to 2019, while Africa, South Asia, and Central America experienced an increase. However, not all forms of crime followed this trend; for instance, an exception being organized crime and corruption which decreased in sub-Saharan Africa and increased in North and Latin America, Australia, and parts of Europe.…”
Section: Crime Trendsmentioning
confidence: 99%
“…Edge et al [1] defined crime as intentional committing an act which is socially harmful and is precisely defined, forbidden under the law, and also punishable. Crime is a major global challenge that occurs in various categories, but property crimes, financial crimes, violence crime, and moral crime are some of the most common types of crimes that affect many societies in developing countries especially Africa and Latin America [2]. Despite a crime to have many variables, unemployment has been mentioned in many social and criminology literatures as one of the common risk factors to the increase in crime especially in the urban societies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, property crime and cybercrime are committed in the USA, Africa (e.g., South Africa, Mali and Nigeria), Latin America (e.g., Mexico), Asia (e.g., Yemen, Afghanistan and Iraq) [ 6 ] and in Canada [ 7 ]. [ 8 ] reported that crime has become a problem in all continents except in Antarctica; however, the highest level of crime was recorded in African, Latin American and Asian countries. Even if the occurrence of crime in the USA is labeled as relatively low by Ref.…”
Section: Introductionmentioning
confidence: 99%